A Visualized and Scientometric Analysis of Health Literacy Research - Wang, Jian; Shahzad, Fakhar (Frontiers in Public Health, 2022)
Purpose: The health literacy concerned by numerous policy and advocacy organizations is springing up rapidly and has evolved substantially over the past few decades. During the period of COVID-19, people who are in the absence of effective treatment and limited availability of vaccination need a higher health literacy to protective themselves. In order to provide a summary of the health literacy research, a visualized and Scientometric analysis is applied in this study. Methods: Based on a scientific review of 3670 data on health literacy from the Web of Science, this research uses Citespace software to systematically and objectively describe health literacy to determine the knowledge evolution structure between articles and investigate research trends. Results: The results show that the annual outputs of publications have grown rapidly since 2003. The USA and Australia make larger contributions compared with other countries in terms of quantity of publications and worldwide collaboration relationship between them. The “Soc sci med,” “J health commun”, “Patient educ couns” and “J Gen Intern Med” pay more attention to health literacy research. The leading authors with influence and authority are Wolf MS, Osborne RH, and Paasche-Orlow MK. Health literacy research in this field focuses on care, knowledge, and education, and so on. An emerging trend of health literacy with Covid-19, online tools, nursing, and obesity will spread across the globe. Conclusion: Compared with simply reviewing existing articles, the major contribution in this study is a comprehensive review of yearly scientific output, journals, countries, institutions, contributors, highly cited papers, and keywords for health literacy research. The review also provides valuable and seminal guidelines for interested researchers on health literacy research.